Tissue optical clearing: State of the art and prospects - Genina, Elina A. (Diagnostics)
The term “tissue optical clearing” (TOC) came into use at the end of the 20th century and is associated with the development of methods for controlling tissue scattering properties using the refractive index matching effect. However, the first mention of increasing the transparency of biological tissues using immersion agents can be attributed to the work of Spalteholz in 1914, in which an organic solvent-based technique was applied to tissue samples in vitro. The next step was made by Barer et al., in 1955, who proposed the optical clearing of cell suspensions by means of protein solution with the same refractive index as the cell cytoplasm.